Primary Productivity Needs For Fish Species Catched By Ring Seweets On Inka Mina Ship In Indonesian Fisheries Port Kwandang District - Djamil, Cahniar; Hamzah, Harisa; Dali, Franki (Agrikan Jurnal Agribisnis Perikanan, 2022)
The purpose of this study to determine the need for Primary Productivity Catch Fish Species Trawl Boat Ring On Mina Inka North Gorontalo District 2022. The research method used is descriptive method done through direct observation with the aim of identifying Primary Productivity as a basis for planning research . Based on calculations, Primary Productivity shows the variation in the year 2014 amounted to 148 630 kg produced , has decreased in 2022 only produced 125 707 kg , while in 2021 only producing 11,950 . The results varied menunjukksn productivity .. View Primary Productivity Needs Ship Inka Mina abundant , the necessary attention from more serious institution for management.